Feeding ecology and interactions of invasive vendace and DR whitefish in the Pasvik watercourse - Høstmark, Malin Solheim (UiT Norges arktiske universitet, 2021)
Introductions and invasions of species outside their natural range can have devastating effects on the native species and be a major driver of biodiversity change. When the zooplanktivorous vendace invaded the Pasvik watercourse in the 1990s, it quickly took over the ecological role of the native DR whitefish. In the upper part of the watercourse, DR whitefish was displaced from the pelagic habitat and food resources, whereas in the lower part, the invasion developed at a slower rate and the two fish species have been able to coexist. Heavy predation from vendace led to the disappearance of the biggest cladoceran species in the watercourse and the remaining species have shifted towards smaller body sizes. The present study explores how the zooplankton community differ in density and composition and how the diet utilization and resource partitioning of pelagic vendace and DR whitefish vary among three contrasting lake sites; Ruskebukta and Tjærebukta in the upper and Skrukkebukta in the lower part of the watercourse, over four different study years. Further, the study explores whether inter-annual temperature variations can explain the variations in body size of Bosmina spp. and Daphnia sp. Samples were collected in September in the four study years in the pelagic zone of the three localities. Stomach content from all vendace and DR whitefish individuals were analyzed and zooplankton species were identified and measured in both the stomach and the environment samples. A key finding was that the zooplankton communities and the fish diets in Tjærebukta and Skrukkebukta were similar to each other in all study years, as opposed to Ruskebukta, where Bosmina spp. was almost depleted from the locality and DR whitefish was chiefly displaced from the pelagic zone and its resources. The body sizes of Bosmina spp. and Daphnia sp. could not be correlated to inter-annual temperature variations. The study revealed strong zooplankton predation and interspecific competition following the vendace invasion, but the impacts largely ...